Genetic polymorphism of sterol transporters in children with future gallstones - Markku J.Nissinen; Niina Pitkänen; Piia Simonen; Helena Gylling; Jorma Viikari; Olli Raitakari; Terho Lehtimäki; Markus Juonala; Mikko P. Pakarinen (Elsevier B.V., 2022)
Conclusions
Risk trait of cholesterol metabolism (low phytosterols) in childhood favouring cholesterol gallstone disease later in adulthood is influenced by risk variant 19H of ABCG8 and obviously also other factors. NPC1L1 variants have minor influence on noncholesterol sterols.